PENGARUH TINGKAT PEMAHAMAN DOSEN UNISKA MAB TERHADAP PERENCANAAN KEUANGAN KELUARGA ISLAMI - Iman Setya Budi; Abdul Wahab; Zakiyah (Wahana Islamika: Jurnal Studi Keislaman, 2021)
In Islam, there is no prohibition for humans to fulfil their needs or desires, as long as these fulfillments can be maintained and their dignity is enhanced. Fulfilment of needs or desires is allowed if it adds maslahah or does not bring harm. Indonesian people are classified as more consumptive when compared to other Southeast Asian countries. The habit of Indonesian people are more likely to use money to meet unimportant needs by behaving consumptively. So people must change their perspective that what must be managed in the family is a financial problem. Because finance is very important in domestic life. To support the welfare of everyone in a family, knowledge of financial planning and management is known, which is called wealth management. So that family financial planning can be effective, efficient, and full of blessings. Therefore, the purpose of this study is to determine the level of  understanding of UNISKA MAB lecturers on Islamic family financial planning affects. This research is field research (field research) with a total sample of 57 people, the technique used is nonprobability sampling, namely purposive sampling, sampling techniques with certain criteria, namely permanent lecturers of UNISKA MAB. As for the data analysis method, the compilers used descriptive statistical methods and Simple Linear Regression Analysis. The results showed that the t-test results for the level of understanding variable showed the t value of 5,053 with sig. t is 0.000 (p <0.05), which means that it has a significant influence on the level of understanding of Islamic family financial planning. So, it can be said that the permanent lecturers of UNISKA MAB already understand Islamic family planning.